(untitled) (Faridpur Medical College Journal, 2021)
Optimal growth and development of a child depends mostly on proper breastfeeding and complementary feeding practices. However, many children yet suffer from malnutrition and the recommended practices of complementary feeding have yet not been established among the majority of the population. In this observational study, we looked for the causes behind the improper complementary feeding practices among the mothers attending the outdoor and indoor units of the Department of Pediatrics, Faridpur Medical College Hospital, Faridpur, Bangladesh, from January 2018 to January 2019. A total of 447 mothers were interviewed regarding their complementary feeding practices and data were analyzed to find out the demographic and social influences. The majority of the respondents were between the age group of 21-25 years (54%). Thirty five percent were illiterate, 60% were from the rural area, 78% were housewives, 64% came from a nuclear family, and 87% had a monthly family income of 5000-20000. Most of the deliveries were conducted at home (58%) and the most common source of feeding related information was healthcare workers (66%). Only 41% of the mothers started complementary feeding at the age of 6 months. The most common complementary food was Suji, 60% of them lacked the knowledge of food preparation and 35% of them practice forceful feeding to the children. The promotion of proper complementary feeding needs to be ensured to achieve the children’s catch-up growth and development. Faridpur Med. Coll. J. 2021;16(1):30-33